Hubungan Terpaan Promosi Instagram @officialfdxbeauty dengan Minat Berkunjung ke Event X Beauty - Auroro, Gracia Groria; Anggara, Reddy; Susanto, Tri (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study aims to analyze the relationship between social media promotion exposure on Instagram @officialfdxbeauty and the interest in visiting the X Beauty Event, using the AIDA (Attention, Interest, Desire, Action) theory. A quantitative approach was used by distributing questionnaires to 100 respondents who are followers of the @officialfdxbeauty account. The results of the Pearson Product Moment correlation test show a significant, strong, and positive relationship between the three sub-variables of promotion exposure, namely intensity, message content, and appeal, with the interest in visiting the X BeautyEvent. The findings indicate that promotion content delivered through the @officialfdxbeauty account, in terms of frequency, clarity of information, and visual and emotional appeal, effectively captures attention, builds interest, generates desire, and encourages actual actions from the audience. Thus, the higher the intensity of exposure to promotional content, the more interesting and relevant the message content, and the stronger the visual and emotional appeal, the higher the interest in attending the X Beauty Event. This confirms that Instagram is an effective medium in supporting digital marketing communication strategies, especially in shaping the interest in visiting an event.